Federalismo fiscal, indicadores socioeconômicos e identidade partidária na distribuição de transferências voluntárias da União: uma proposta de modelo de previsão para os municípios brasileiros (2010-2021) - Andrade, Rafael Resende de (2024)
Objective: This study aims to investigate how socioeconomic indicators and party identity influenced, in light of the theory of fiscal federalism, the allocation of voluntary transfers from the Union to Brazilian municipalities between 2010 and 2021. Methodology: This is a quantitative study that seeks to test hypotheses and propose a predictive model for federal voluntary transfers to municipalities through descriptive analysis, multiple linear regression, and logistic regression. Main Results: The expectation is that voluntary transfers from the Union do not prioritize municipalities with lower socioeconomic indicators and are also influenced by the party alignment between the President of the Republic and the municipal mayor. Relevance and Originality: While academic literature maintains interest in this topic, studies linking fiscal federalism, socioeconomic indicators, party identity, and voluntary transfers to municipalities remain scarce, underscoring the relevance and originality of this work. Theoretical, Methodological, and Management Contributions: This research aims to offer theoretical contributions by establishing a relationship between fiscal federalism theory, party identity, and discretionary intergovernmental transfers, as well as practical contributions by presenting a predictive model to prioritize the neediest municipalities in Brazil. Social Contribution: The results confirm that the party identity between the municipal mayor and the President of the Republic influences the distribution of voluntary transfers, with a higher volume of funds tending to concentrate in municipalities with higher GDP or GDP per capita, while socioeconomic indicators (IDHM and IDSC) do not significantly affect this allocation.